A novel gene insertion combined with a missense mutation causing factor VII deficiency in two unrelated Chinese families. Issue 6 (September 2015) - Hao, Xiuping; Cheng, XiaoLi; Wang, Yingyu; Yang, LiHong; Xie, Yaosheng; Wang, Mingshan; Jin, Yanhui
<x xml:space="preserve">Abstract</x> Hereditary coagulation factor VII (FVII) deficiency is a rare bleeding disorder characterized by reduced FVII activity (FVII:C) and inconsistent FVII antigen (FVII:Ag). In our study, two pregnant probands were diagnosed with FVII deficiency, based on the tests that FVII:C were both 3% and FVII:Ag were less than 7.5%. Gene sequencing revealed the same compound mutations, a recurrent missense mutation p.Arg277Cys and a novel insertion mutation g.11520–11521insT. What is more, haplotype analysis of SNPs excluded the possibility of consanguinity between the two families. According to the model, we speculated that although the insertion mutation was close to the carboxy-terminal, it induced the protein extension and affected the 3′ untranslated region of F7 gene, which is significant to posttranscriptional regulation. Hypothetically, the stability or translational efficiency of mRNA may be influenced, resulting in reducing FVII:C.